Co-Payments in Respect of Prescribed Minimum Benefits (PMBs) in South African Medical Schemes - Moabelo, Matlou Martin (University of the Witwatersrand, Johannesburg, 2024)
Background: In the South African medical insurance market, the cost of Prescribed Minimum Benefits (PMBs) has been increasing. The Council for Medical Schemes (CMS) report shows that total out-of-pocket payments (OOP) (including for PMBs) rose to R35 billion in 2019 from R25 billion in 2015. The rising cost of PMBs affects the financial stability of medical schemes, but it also has an impact on members through an increase in out-of-pocket payments (co- payments, deductibles etc) as part of cost sharing, and these payments are more likely to adversely affect the affordability of healthcare. This study aimed to quantify the extent of PMB co-payments, and the factors associated with it as well investigate PMB-related complaints. Methods: This study used quantitative longitudinal data from the CMS. Descriptive and multiple regression methods were employed to analyse PMB co-payments among a sample of 5.14 million PMB patients for the period 2015 to 2019 and 244 complaints in 2019. The PMB co-payment was calculated using both a narrow and broader definition. The narrow definition of PMB co-payments focused solely on the out-of-pocket funding while the broader definition refers to the amount funded out-of-pocket plus from savings accounts (OOP+SA co-payment). Results: The estimated overall OOP co-payment amounted to R4.65 billion in 2019 and R4.74 billion for OOP+SA co-payment. The average PMB co-payment per member amounted to R905.47 [95% CI:903.88-907.07] per annum (OOP co-payment), and R922.06 [95% CI: 920.42- 923.69] for OOP+SA co-payment. The average OOP co-payment for chronic conditions (CDLs) per member was R310.07 (95% CI:308.17-311.96), and for the OOP+SA co-payment it was R318.47 (95% CI:316.57-320.37). There has been an increasing upward trend in PMB co- payments from R583.86 in 2015 to R922.06 in 2019 (p=0.0275). The regression analysis indicated that PMB co-payment varied by benefit design, age group, gender, setting, province, and scheme type. The analysis of the PMB complaints revealed that excessive PMB co- payments were caused by medical schemes failing to comply with PMB regulations, and patients not understanding the PMB rules or opting not to obey the rules. Conclusions: Medical scheme members pay substantial PMB co-payments due to medical schemes and patients not adhering to PMB regulations. To mitigate these co-payments, it’s essential to educate members on PMB rules and enforce penalties on medical schemes that do not comply with PMB regulations.
A research report submitted in fulfillment of the requirements for the Master of Public Health, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Co-payment; Prescribed Minimum Benefits; OOP co-payment; medical schemes; SDG-3: Good health and well-being